Internationalization Processes of Multichannel Retailers and E-tailers in the Apperal Industry: A Comparative Case Study - Batur, Aysu; CELIK, Asiye Ayben (International Journal of Contemporary Economics and Administrative Sciences, 2021)
In order to explore the internationalization of Turkish apparel retailers, with this study it is aimed to comparatively analyze the motivations underlying the internationalization processes of Turkish multi-channel retailers and e-tailers in Turkish apparel industry in terms of internationalization process, management of foreign operations, critical success factors and international e-commerce activities. Holistic multiple case study method was adopted in the research and the cases were determined through purposive sampling. The data gathered by semi-structured interviews, were analyzed with thematic-constructive content analysis method. The findings obtained from the research reveal that multi-channel apparel retailers and e-tailers go through different internationalization processes as a result of their internationalization motivations, way of entering foreign markets, and the size of their organizational structures due to the business model they have adopted. In addition, the management of operations in foreign markets, success factors in foreign markets were found to be similar. The study contributes to the practitioners as a guide at the point of defining internationalization strategies, managing international operations, using online channels in international markets, identifying the factors that they should prioritize for success in the international market.